Measuring childhood disability and AIM programme provision in Ireland - Adele Whelan; Adele Bergin; Anne Devlin; Abian Garcia Rodriguez; Séamus McGuinness; Ivan Privalko; Helen Russell (The Economic and Social Research Institute (ESRI), 2021)
The social inclusion of children with disabilities, and in particular their inclusion in early learning and care settings, is key to maximising their wellbeing, care and future education. It is therefore vital that children with disabilities have equal access to early learning and school age care and education. Joint research, published by the ESRI and Pobal explores a number of existing challenges experienced by children with disabilities in this area.
Keywords: 330